Global Impact of Peripheral Obstructive Arterial Disease in Portugal: An Eight Year Study - Mariana Moutinho; Inês Simões; Sónia Rodrigues; Daisy Abreu; Emanuel Silva; Paulo Sousa; José Fernandes e Fernandes (Acta Médica Portuguesa, 2019)
Introduction: Peripheral arterial disease has an important impact on morbidity/mortality. The objective of this study was to quantify the impact of this disease in Portugal during the last eight years, expressed by the volume of admissions, treatment strategies and associated morbidity and mortality. Material and Methods: We collected data from the Diagnosis Related Group national database on primary diagnosis, procedures codes, demographic variables, a number of risk factors, and mortality of all cases admitted from 2009 to 2016 with a primary diagnosis of peripheral arterial disease coded according to the 9th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-9). Results: In this study, peripheral arterial disease led to 27 684 hospitalisations, which corresponded to 26.7% of all admissions for vascular disease in this period. Approximately 49.9% of patients were admitted to the emergency department. The volume of procedures in patients with claudication decreased over the eight years, unlike patients with critical ischaemia, in which the number of procedures increased. Discussion: Age and the presence of cardiovascular risk factors have been associated with the severity of disease, as observed in our series. Overall hospital mortality varied, being significantly higher in patients with more advanced severity of the disease. Conclusion: Peripheral arterial disease represents an important burden in the overall volume of admissions in Portuguese public hospitals. A large number of patients was admitted in the context of emergency.